Learning Community Management in Improving Teachers’ Pedagogic Competency - Sudiati, Sudiati; Widayatsih, Tri; Eddy, Syaiful (Yayasan Sembilan Pemuda Indonesia, 2025)
The purpose of this study was to analyze the management of learning communities in improving teachers’ pedagogical competence, the challenges faced in conducting learning community programs, and analyzing solutions in overcoming the challenges of learning community programs at State Elementary School 229 Plaju Palembang City. One of the key factors in improving teachers’ pedagogical competence is teacher collaboration in learning communities with good planning, organization, implementation, and supervision. The research method used is a qualitative approach using data collection techniques such as observation, interviews, and documentation. Results show that 85% of teachers improved pedagogical skills through collaborative programs, though challenges like time constraints (reported by 70% of participants) persisted. The results show that learning community management has been implemented in a systematic and participatory manner, involving careful planning, data-based needs analysis, and implementation of relevant professional programs. This activity has the support of the principal and lead teachers, with a clear organizational structure and a strong culture of collaboration as reinforcing factors. The research also found various challenges in its implementation, such as limited time, human resources, member participation, and funding, which impacted the effectiveness and sustainability of the program. However, adaptive management strategies, the use of technology, the formation of interest-based work teams, and regular reflection overcame these challenges. The CERDIK learning community has proven to be an effective platform for teacher professional development and an example of good practice in the primary school environment.